RIGHT INFRAUMBILICAL VERSUS LEFT INFRA /SUPRAUMBILICAL ACCESS FOR CREATING OPEN PNEUMOPERITONEUM IN LAPAROSCOPIC CHOLECYSTECTOMY: A PROSPECTIVE COMPARATIVE STUDY (Asian Journal of Medical Research and Health Sciences, 2026)
Introduction: Laparoscopic cholecystectomy is the standard treatment for symptomatic gallstone disease, and creation of pneumoperitoneum is a critical step for providing adequate intra-abdominal visualization and instrument manoeuvrability. The open technique is widely used for controlled peritoneal entry. However, comparative data regarding the simplest and most effective site for first-port creation by the open technique remain limited. The present study compared different first-port sites during laparoscopic cholecystectomy. Objectives: To determine the simplest and most effective site for creation of the first port and pneumoperitoneum by the open technique during laparoscopic cholecystectomy, and to compare the approaches with respect to duration of port creation, surgeon position, complications, hospital stay and postoperative recovery. Methodology: This prospective comparative study was conducted among 100 patients undergoing laparoscopic cholecystectomy. The study compared open first-port placement using the infraumbilical and supraumbilical approaches, with assessment of the right- and left-sided approaches as described in the study protocol. Demographic characteristics, surgeon position, duration of first-port creation, duration of hospital stay, port-site infection, port-site hernia, bowel injury, biliary tree injury and days to resumption of normal activity were recorded. Statistical analysis was performed using chi-square testing, with p